Redirection of miRNA‐Argonaute Complexes to Specific Target Sites by Synthetic Adaptor Molecules. Issue 7 (25th June 2020) - Bolz, Mathias; Thomas, Laura; Scheffer, Ute; Kalden, Elisabeth; Hartmann, Roland K.; Göbel, Michael W.
Abstract: Dysregulation of miRNAs is connected with a multitude of diseases for which antagomirs and miRNA replacement are discussed as therapeutic options. Here, we suggest an alternative concept based on the redirection of RISCs to non‐native target sites. Metabolically stable DNA‐LNA mixmers are used to mediate the binding of RISCs to mRNAs without any direct base complementarity to the presented guide RNA strand. Physical redirection of a dye‐labeled miRNA model and of specific miRNA‐programmed RISC fractions present in HeLa extracts is demonstrated by pull‐down experiments with biotinylated capture oligonucleotides. Abstract :